2005
DOI: 10.4028/www.scientific.net/msf.475-479.353
|View full text |Cite
|
Sign up to set email alerts
|

Microstructures and Thermal Stability of the Metastable-Phase Precipitates Formed in an Al-Cu Alloy

Abstract: The precipitation behavior in an Al-Cu alloy isothermally annealed at 373K~493K was studied, using the Vickers microhardness tests, Differential scanning calorimetry(DSC) and Transmission electron microscope(TEM) observations. An additional endothermic peak was found in DSC measurements which may be attributed to the θ″-phase independent from the formations of the G.P.(Ⅱ) and the θ′-phase at the aging temperatures. High resolution transmission electron microscopy (HRTEM) revealed that the G.P.(Ⅰ) is formed at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…After passing over the plateau, the curve again increased until it attained a peak hardness in the third stage after aging for 3:0 Â 10 7 s. In the fourth stage, the HV hardness decreased with aging time. Figure 2 shows the DSC curves with endothermic reactions that are attributed to the dissolution of metastable phases in an Al-1.94 at%Cu specimen aged at 373 K. Systematic DSC measurements at various times up to 3:0 Â 10 7 s revealed the existence of three endothermic peaks in the DSC thermograms under 550 K. From the interpretation in previous papers, [5][6][7] we concluded that the first endothermic peak corresponds to the dissolution of solute clusters, the second to G.P. (I) dissolution, and the third to G.P.…”
Section: Methodsmentioning
confidence: 65%
See 2 more Smart Citations
“…After passing over the plateau, the curve again increased until it attained a peak hardness in the third stage after aging for 3:0 Â 10 7 s. In the fourth stage, the HV hardness decreased with aging time. Figure 2 shows the DSC curves with endothermic reactions that are attributed to the dissolution of metastable phases in an Al-1.94 at%Cu specimen aged at 373 K. Systematic DSC measurements at various times up to 3:0 Â 10 7 s revealed the existence of three endothermic peaks in the DSC thermograms under 550 K. From the interpretation in previous papers, [5][6][7] we concluded that the first endothermic peak corresponds to the dissolution of solute clusters, the second to G.P. (I) dissolution, and the third to G.P.…”
Section: Methodsmentioning
confidence: 65%
“…Since it was clarified in previous reports by the present authors [5][6][7] that four types of metastable phase precipitates are formed before the intermediate 0 phase formation, we have adopted a new interpretation of the precipitation sequence in an Al-Cu alloy: supersaturated solid solution (ssss) ! solute clusters !…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation